The Impact of Physical Activities on Male Fertility: A Systematic Review - Kapla, Albert; Černohorská, Alicja; Bednarczyk, Daria; Białeta, Julia; Siembab, Karolina; Rowińska, Katarzyna; Jurkiewicz, Michalina; Garbarczyk, Wiktor; Pysiewicz, Wiktoria; Napieralska, Agnieszka (Quality in Sport, 2025)
Background Semen quality appears to have declined over the past decades but reasons for this decline are unresolved. It may seem that an increase in the share of a sedentary lifestyle, at least due to the way of working or spending free time, and a decrease in the share of physical exercises during everyday activities may have an impact on this. The objective of this study was to evaluate the relationship of physical activity, special types of physical activity and sedentary lifestyle with sperm parameters in a population of men. Another issue discussed is the negative impact of exercise on fertility, as well as injuries in the perineal region—some of which directly affect organs, surrounding tissues (such as nerves), and regulatory mechanisms like hypothalamic-pituitary-gonadal axis. Materials and Methods This study was conducted as a comprehensive literature review based on scientific articles and research papers accessed through two primary databases: PubMed and Google Scholar. Relevant articles were selected using predefined keywords and phrases related to the study’s topic. The search was limited to articles published in English between 1991 and 2023 to ensure the relevance and accuracy of the data. Duplicates, non-peer-reviewed sources, and studies lacking methodological transparency were excluded. The collected data were analyzed and synthesized to provide an up-to-date overview of the topic. Conclusion The authors argue that the generally positive impact of exercise on male fertility can be demonstrated on many levels. However, moderation in training load is necessary, as excessive training volume can lead to hormonal regulation issues or simply result in injury in the groin area.